Evaluation of Hydrocarbon Source Rock Potential and Organic Geochemistry in North Arafura Shelf, Papua (Indonesia) - Sabra, Eriko (Geological Agency, 2021)
The results of this study identified two potential source rock intervals of Permian age in the North Arafura Shelf area of Papua, Indonesia. The first potential source rock interval (SR-1) was identified at 3834.9 m to 3838.6 m depth within the Kola-1 well, which is believed to be good to very good potential source rock with TOC in the range of 2.94 to 3.4 wt %, S1 0.78 to 0.97 mg HC/g, and S2 5.63 to 9.5 mg HC/g. The source rock is composed of type II and III kerogens with HI in the range of 164 to 275 mg HC/gTOC and reached the maturation stage with Ro of 0.83 - 0.86%, Tmax of 442 - 444 C, and Production Index (PI) of 0.09 - 0.12. The second potential source rock interval (SR-2) is at 3060.1 - 3136.3 m depth in the ASM-1X well and has fair potential to be source rock with TOC of 0.95 wt %, S1 of 1.01 mg HC/g, and S2 of 3.39 mg HC/g. This source rock has type II kerogen with a HI value of 357 mg HC/g TOC and has reached maturation as indicated by a Ro value of 0.63%, Tmax of 430 C, and PI of 0.23. Biomarker analysis revealed SR-1 is type III kerogen with terrigenous input and was deposited in an estuarine environment.